The Role of science, technology and innovation in ensuring food security by 2030 (UN US, 2017)
Identifies, analyses and presents for discussion key issues concerning the role of science, technology and innovation (STI) in ensuring food security by 2030, particularly in developing countries.
Keywords: FOOD SECURITY